Analysis of the Effect of Compensation and Work Environment on Employee Discipline at PT Sinar Sawit Subur Lestari - Wilda Afrizal; Muhammad Irwansyah Hasibuan (SAINTIS Publishing, 2026)
This study analyzes the influence of compensation and the work environment on employee discipline at PT Sinar Sawit Subur Lestari. Work discipline is considered crucial for increasing organizational productivity, particularly in the palm oil plantation industry, which demands compliance and responsibility. The research method used was quantitative with saturated sampling, involving 80 employees as respondents. Data were collected through a Likert-scale questionnaire, and analysis was conducted using multiple linear regression with SPSS version 25. The results show that compensation has a positive and significant effect on employee discipline, with a t-value of 8.001 and a significance level of 0.000. This indicates that a fair compensation system can increase employee motivation and compliance. However, the work environment did not show a significant effect, with a t-value of 0.267 and a significance level of 0.790. Conversely, simultaneously, compensation and the work environment had a significant effect on employee discipline, with an F-value of 71.694 and a significance level of 0.000. The coefficient of determination indicates that these two factors explain 64.2% of the variation in employee discipline. This study recommends that companies improve transparent compensation systems and create a supportive work environment to strengthen employee discipline in a sustainable manner.